Implementation of the Bugis Sipatuo Sipatokkong Culture in Strengthening Social Values in Students in Elementary Schools - Sudarmin; Dideng Kadir (Ikatan Dosen Sains dan Teknologi Indonesia, 2025)
Education plays a crucial role in preserving and transmitting local wisdom while addressing contemporary challenges such as increasing individualism, declining social values, and the erosion of cultural identity among elementary school students. In the context of globalization and digitalization, local cultural philosophies are often marginalized in formal education, despite their strong potential to support character formation and social cohesion. This study aims to examine the implementation of the Bugis–Makassar cultural philosophy Sipatuo Sipatokkong as a framework for strengthening students’ social values in an elementary school setting. A qualitative descriptive approach was employed, involving purposive sampling of principals, classroom teachers, students, and traditional community leaders at a public elementary school in South Sulawesi, Indonesia. Data were collected through participant observation, in-depth unstructured interviews, and document analysis, and were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings reveal that the values of Sipatuo Sipatokkong, including mutual cooperation, mutual reminding, mutual support, and mutual respect, are effectively internalized through daily learning activities, school routines, and social interactions. These values contribute to positive behavioral changes, such as increased empathy, collaborative learning, respectful communication, and reduced individualistic tendencies among students. The novelty of this study lies in its integrative approach, which translates a specific local cultural philosophy into observable pedagogical practices across both intra-curricular and extra-curricular domains. The study concludes that Sipatuo Sipatokkong functions not merely as cultural heritage but as a viable pedagogical framework for character education. This research contributes to the field of local wisdom in education by providing an empirically grounded model for integrating indigenous cultural values into formal schooling, offering practical implications for educators and policymakers seeking to promote culturally responsive, socially meaningful, and sustainable education.